Development strategy toward renewable energy society: Integrating energy potential, efficiency, and community awareness - Noor Wibawa (Journal of Innovation Materials, Energy, and Sustainable Engineering, 2026)
Background: Energy demand continues to rise in line with global population and industrial growth. In Indonesia, approximately 87.3% of total energy supply is still generated from fossil-fuel-based power plants, leading to high CO₂ emissions and environmental degradation. Despite its abundant renewable resources, such as hydropower, solar, and wind, the national transition toward clean energy remains slow. This study aims to examine strategic pathways to accelerate renewable energy development and establish a renewable energy–based society in Indonesia. Methods: This research employs a quantitative approach using secondary data derived from previous studies and official national statistics to evaluate Indonesia’s greenhouse gas (GHG) emission profile and renewable energy potential. Analytical techniques include the driver pressure state impact response (DPSIR) framework to assess causal relationships between human activities and environmental impacts, complemented by logical framework analysis (LFA) to identify the root causes hindering the adoption of renewable energy technologies. Findings: The study reveals that Indonesia possesses sufficient renewable energy resources to substitute existing coal-fired power plants entirely through the optimization of hydropower, solar, and wind energy systems. However, the transition process is hindered by multiple challenges, including technical limitations, financial constraints, and inconsistent policy implementation. The findings also emphasize the importance of community awareness, sustainable urban planning, and electrification of transportation systems to support nationwide decarbonization efforts. Conclusion: The development of a renewable energy society integrating energy efficiency, environmental awareness, and policy reform constitutes a critical step toward achieving a sustainable and climate-resilient future for Indonesia. Novelty/Originality of this article: This study introduces a holistic framework for establishing a renewable energy society in Indonesia by combining the DPSIR and LFA analytical methods. The proposed framework not only identifies systemic barriers but also outlines practical and policy-based strategies to accelerate the national energy transition while maintaining social, economic, and environmental sustainability.